Expanding the gelation properties of valine-based 3,5-diaminobenzoate organogelators with N-alkylurea functionalities - Chow, Hak-Fun; Cheng, Chin-Ho (Beilstein Journal of Organic Chemistry, 2010)
A new family of valine-containing 3,5-diaminobenzoate derivatives 2 with N-alkylurea moieties attached to the valine moieties was prepared. By appending these two new N-alkylurea chains to the molecular structure, their organogelating properties were extended from only aromatic solvents, to a wide range of other types of solvents such as alicyclic hydrocarbons, alcohols and polar solvents such as DMSO and DMF. It was also found that a longer N-alkylurea chain conferred improved gelation power and higher thermal stability as compared to those of the shorter ones.
Keywords: amino acids; hydrophobic effect; organogelators; self-assembly; urea